The American Evangelic Mission and the Women education in Egypt 1853 - 1900 - Elsabbagh, Abdellatif Mohammed (Journal of Posthumanism, 2025)
Education is the most important means of the Evangelic Church for evangelization in Islamic countries that have Orthodox minorities, such as Syria, Lebanon, and Egypt. The Evangelic Church began its activity in Syria, from which (then) it set out to Egypt with a delegation that visited Alexandria, Cairo, and Upper Egypt, in 1824. The delegation monitored the educational conditions and noticed that there were no schools for girls. Then, the Evangelic Church decided to start its missionary activity in Egypt, in 1853, and used education as a means to spread the Protestantism among the Orthodox. In this research, the researcher seeks to monitor the efforts of the Evangelic Mission to educate girls in Egypt. The researcher also discusses how this mission was able to move into this thorny field, in spite of being operating in a new conservative environment. The mission succeeded to persuade the new Protestants to educate their daughters, joined after that by the girls of the upper-class Muslims. The Evangelic mission also provided home education to the Egyptian women; it started by adult education, which consider revising as a practical way to persuade society to educate girls. By the end of the nineteenth century, the Evangelical Mission succeeded in forming the first pioneers of education in Egypt.